Arbitrage, Hedging, and Financial Innovation - Dow, James (Review of Financial Studies, 1998)
[I consider the costs and benefits of introducing a new security in a standard framework where uninformed traders with hedging needs interact with risk-averse informed traders. Opening a new market may make everybody worse off, even when the new security is traded in equilibrium. This article emphasizes cross-market links between hedging and speculative demands: risk-averse arbitrageurs can use the new market to hedge their positions in the preexisting security, which can affect liquidity in the old market. More generally, the availability of such hedging opportunities will influence the strategies to which traders will direct resources.]